`@` `\text {Ans}`
`\downarrow`
`a)`
\(x \times 27 + x \times 83 = 23400\)
`x \times (27 + 83) = 23400`
`x \times 110 = 23400`
`x = 23400 \div 110`
`x = 2340/11`
Vậy, `x = 2340/11`
`b)`
`x \times 153 - x \times 53 = 7600`
`x \times (153 - 53) = 7600`
`x \times 100 = 7600`
`x = 7600 \div 100`
`x = 76`
Vậy, `x = 76.`
a: =>x*110=23400
=>x=2340/11
b: =>100x=7600
=>x=76
a) \(x\times27+x\times83=23400\)
\(x\times\left(27+83\right)=23400\)
\(x\times110=23400\)
\(x=23400:110\)
\(x=\dfrac{2340}{11}\)
b) \(x\times153-x\times53=7600\)
\(x\times\left(153-53\right)=7600\)
\(x\times100=7600\)
\(x=7600:100\)
\(x=76\)